2022
DOI: 10.1155/2022/1058813
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Biomarkers and Their Association with Mortality among Patients Infected with SARS-CoV-2 in Mexico

Abstract: Background. Activation of the immune system response is associated with the generation of oxidative stress (OS). Several alterations are involved in OS, such as excessive production of reactive oxygen species (ROS) and decreased antioxidant activity, which together lead to an imbalance in redox status. The role of OS during SARS-CoV-2 infection is not fully understood. The aim of this study was to determine OS biomarkers and assess their usefulness as a predictor of mortality in COVID-19 patients. Methods. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
3
9
0
Order By: Relevance
“…This result was in concordance with the findings of Shakaroun et al 52 Oxidative imbalance in COVID-19 patients can be determined by measuring oxidative stress biomarkers such as MDA and antioxidant biomarkers. Our study shows a higher level of MDA in the critical group than in HCs, this is consonance with the published work by Avila-Nava et al, 25 Mehri et al 53 The reason for increasing MDA may be due to high levels of free radicals in COVID-19 that accelerate the rate of lipid peroxidation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result was in concordance with the findings of Shakaroun et al 52 Oxidative imbalance in COVID-19 patients can be determined by measuring oxidative stress biomarkers such as MDA and antioxidant biomarkers. Our study shows a higher level of MDA in the critical group than in HCs, this is consonance with the published work by Avila-Nava et al, 25 Mehri et al 53 The reason for increasing MDA may be due to high levels of free radicals in COVID-19 that accelerate the rate of lipid peroxidation.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have stated the high level of OS and deficient antioxidant biomarkers in COVID-19 patients. 25–27 However, these investigations do not provide adequate justification for the use of antioxidant parameters as diagnostic and prognostic biomarkers. Therefore, the goals of the current study are to determine the impact of OS on COVID-19 sufferers through the measurement of hematological, inflammatory, coagulation, and oxidative/antioxidant biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies confirmed a decrease in Se and associated components in patients with COVID-19 disease [ 27 , 28 , 29 , 30 ]. The results of our study indicate that hospitalized COVID-19 patients had reduced levels of Se in their blood plasma, which were lower than the European healthy adult reference ranges of 70–130 μg/L (median 87 μg/L) for Se concentration, with concentrations below 70 μg/L considered deficient [ 6 ].…”
Section: Discussionmentioning
confidence: 92%
“…Strong positive correlations between lipid peroxides and Cu and the negative correlation between γ-tocopherol and Cu highlighted the role played by copper in increased oxidative stress in COVID-19 patients. Oxidative stress is increased in patients with COVID-19 and is associated with mortality ( 21 ).…”
Section: Discussionmentioning
confidence: 99%